Epidemiological and virological characteristics of influenza B: results of the Global Influenza B Study. (August 2015) - Caini, Saverio; Huang, Q. Sue; Ciblak, Meral A.; Kusznierz, Gabriela; Owen, Rhonda; Wangchuk, Sonam; Henriques, Cláudio M. P.; Njouom, Richard; Fasce, Rodrigo A.; Yu, Hongjie; Feng, Luzhao; Zambon, Maria; et al.
Abstract : Introduction: Literature on influenza focuses on influenza A, despite influenza B having a large public health impact. The Global Influenza B Study aims to collect information on global epidemiology and burden of disease of influenza B since 2000. Methods: Twenty‐six countries in the Southern ( n  = 5) and Northern ( n  = 7) hemispheres and intertropical belt ( n  = 14) provided virological and epidemiological data. We calculated the proportion of influenza cases due to type B and Victoria and Yamagata lineages in each country and season; tested the correlation between proportion of influenza B and maximum weekly influenza‐like illness (ILI) rate during the same season; determined the frequency of vaccine mismatches; and described the age distribution of cases by virus type. Results: The database included 935 673 influenza cases (2000–2013). Overall median proportion of influenza B was 22·6%, with no statistically significant differences across seasons. During seasons where influenza B was dominant or co‐circulated (>20% of total detections), Victoria and Yamagata lineages predominated during 64% and 36% of seasons, respectively, and a vaccine mismatch was observed in ≈25% of seasons. Proportion of influenza B was inversely correlated with maximum ILI rate in the same season in the Northern and (with borderline significance) Southern hemispheres. Patients infected with influenza B were usually younger (5–17 years) than patients infected with influenza A. Conclusion: Influenza B is a common disease with some epidemiological differences from influenza A. This should be considered when optimizing control/prevention strategies in different regions and reducing the global burden of disease due to influenza.